Charlesworth & Percy on negligence (Sweet & Maxwell LondonGB, 2001)
Looks at the general principles and the standard of care. Deals with statutory duty, absolute or strict liability, death and causes of actions as well as miscellaneous matters.
Keywords: LIABILITY